Affective Risk Associated With Menstrual Cycle Symptom Change - Kiesner, Jeff; Eisenlohr-Moul, Tory A.; Vidotto, Giulio (Frontiers in Global Women's Health, 2022)
In the present study we test whether cyclical changes in affective symptoms of the menstrual cycle are associated with higher mean levels of those same symptoms. Using prospective daily reports across two full menstrual cycles, from two samples of female University students (n = 213; n = 163), we applied both quartic polynomial regressions and cosine regressions to model cyclical change in symptoms, and to test for mean-level differences in symptoms across the resulting trajectory patterns. Counter to prior findings, but consistent with theoretical expectations, these results show that females who experience menstrual cycle-related changes in affect (whether a perimenstrual or mid-cycle increase) are at risk for higher average levels of affective symptoms. These results suggest that the mid-cycle group should be recognized as a target for future research that is associated with increased risk for chronic negative affective symptoms.